If Looks Could Kill: Do Characteristics of Female Offenders Influence Death Penalty Sentencing Decisions? - Bell, Conner (Women & criminal justice, 2021)
Sentencing research suggests that offenders who are more physically attractive are more likely to experience leniency in verdict and sentencing. Additionally, there is evidence that other extralegal factors, such as race, influence public and juror opinions on criminality and the appropriate punishment of criminal defendants. Much research on attractiveness, however, has not focused on female offenders or does not explore death penalty opinions. Using a student sample and an online survey with factorial vignettes, this study seeks to examine the likelihood of endorsing the death penalty for a hypothetical female offender relative to her physical attractiveness and race. Results show that attractiveness of the offender did not affect the likelihood of the respondent selecting the death penalty. The race of the offender and victim did affect the likelihood of the respondent selecting the death sentence, with respondents less likely to select the death penalty for African American offenders than white offenders, more likely to select the death penalty in vignettes with African American victims than white victims.